The visual dictionary of flight (Boston, Mass. : New York : Distributed by Houghton Mifflin Co., Boston, Mass. : Distributed by Houghton Mifflin Co., 1992)
Text and labeled illustrations depict a variety of historic and modern aircraft and their components, as well as aviation-related equipment.
Includes index.
Keywords: Airplanes -- Juvenile literature. -- Juvenile literature; Airplanes -- Juvenile literature. -- Juvenile literature; Aeronautics -- Juvenile literature. -- Juvenile literature; Aeronautics -- Juvenile literature. -- Juvenile literature; Picture dictionaries, English -- Juvenile literature; Airplanes; Aeronautics